Price Adjustments and Inflation - Evidence from Norwegian Consumer Price Data 1975-2004 - Fredrik Wulfsberg (Norges Bank, 2009)
I document price adjustments in both high and low inflation years from 14 milllion monthly price observations of 1,133 goods and services. The variation in the frequency of price changes explains all the variation in the inflation rate. On average, prices increase more often when inflation is high, and decrease more often when inflation is low. There is also substantial variation both in the duration and size of price changes within and between items.
hdl:11250/2577448
Keywords: C2; D40; E31; 330; consumer prices; price rigidity